Analysis of Flavor Characteristics of Guizhou Summer-Autumn Black Tea by Fermentation with Artificial Inoculation of "Golden Flower" Fungus - Linyao SONG; Hui XU; Guangcan TAO; Siyao WU; Sen CAO; Lingshuai MENG; Dajuan SHI; Xi CHEN; Degang ZHAO; Xuan DONG; Yichen ZHAO; Su XU (Shipin gongye ke-ji, 2025)
To enhance the value of summer-autumn teas and address the diverse needs of the tea market, this study employed the "Golden Flower" fungus to ferment Guizhou summer-autumn black tea, resulting in the preparation of fermented tea. The sensory quality and chemical composition content of the fermented tea were utilized as comprehensive evaluation indicators to optimize the fermentation process. Additionally, headspace solid-phase microextraction-gas chromatography-mass spectrometry (HS-SPME-GC-MS) technology, orthogonal partial least squares discriminant analysis (OPLS-DA), and odor activity value (OAV) were employed to analyze the changes in volatile compounds before and after fermentation. The results indicated that the optimal preparation conditions for the fermented tea included a moisture content of 34.5%, an inoculation amount of 1.5‰, and an incubation period of 10 days. Under these conditions, the moisture content, total ash content, tea stem content, water extract content, and colony-forming units of the finished fermented tea all met the requirements of China National Standards outlined in GB/T 32719.5-2018 Dark Tea Part 5: Fu Tea. A total of 95 volatile compounds were identified in both the summer-autumn black tea and the finished fermented tea using HS-SPME-GC-MS, including 21 aroma-active compounds (OAV>1), such as 2-ethyl-5-methylpyrazine, acetophenone, linalool oxide Ⅰ, linalool oxide Ⅱ, and β-damascenone, which contributed to the pronounced honey, sweet, and floral aromas of the finished fermented tea. Furthermore, 21 volatile compounds (VIP>1, P<0.05) were identified through OPLS-DA as key differentiators between summer-autumn black tea and the finished fermented tea. This study provides valuable insights for the comprehensive utilization of summer-autumn tea resources and the development of related products.